Overload on the primary caregiver of patients with chronic kidney disease during the SARS-CoV-2 pandemic - Cárabes Espino, Ana Grecia (Universidad de Sonora, 2021)
Introduction: In times of pandemic, with a significant prevalence of chronic non-communicable diseases in Mexico is associated the risk of contracting viral diseases such as SARS-CoV-2, a risk that can be transferred to primary caregivers and increase the demand for daily life care to sick person. Objective: to describe the level of primary caregiver overload of patients with chronic kidney disease who receive renal replacement therapy in a second-level pandemic hospital center. Methodology: Descriptive, cross-sectional study with n = 84, simple random sampling. Results: The age was 54 ± 10 years and the female gender predominated. The majority of people who care for a CKD patient suffer from a chronic disease. A small percentage (23.8%) consider that the overload they have due to functions they perform is intense. Conclusions: Most of the primary caregivers of patients with chronic kidney disease (CKD) who receive renal replacement therapy in a second-level hospital in times of pandemic are perceived without overload. It is necessary to study this phenomenon in greater depth, as well as its impact on the health of the caregiver, since most suffer from a chronic disease and are doubly vulnerable to the spread of the SARS-CoV-2 virus.